2013
DOI: 10.1074/jbc.m113.468967
|View full text |Cite
|
Sign up to set email alerts
|

The Cardioprotective Protein Apolipoprotein A1 Promotes Potent Anti-tumorigenic Effects

Abstract: Background: ApoA1, a component of HDL, promotes anti-inflammatory, immunomodulatory, and cardioprotective functions. Results: ApoA1 suppresses tumor growth and metastasis, primarily via modulation of innate and adaptive immune responses. Conclusion: ApoA1 impacts tumor biology at multiple levels, which appear to be linked to immunomodulatory function. Significance: ApoA1 redirects elicited immune cells toward tumor suppression and rejection and may hold benefit as a cancer therapeutic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
277
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 215 publications
(292 citation statements)
references
References 65 publications
12
277
3
Order By: Relevance
“…Huang, Wang, Zhang, Li, & Li, 2013) Anastellin 256 (Neskey, Ambesi, Pumiglia, & McKeown-Longo, 2008;Pasqualini, Bourdoulous, Koivunen, Woods, & Ruoslahti, 1996;M. Yi & Ruoslahti, 2001) Apolipoprotein A-1 31 (Macuks et al, 2010;Zamanian-Daryoush et al, 2013) Fibrinogen β chain 56 (Krajewska et al, 2010) Keratin type I cytoskeletal 9 62 (W. Yi et al, 2013) Others: Complement component C4b (Childo blood group) 193 (Markiewski & Lambris, 2009;Rutkowski et al, 2010) …”
Section: Biochemical and Immunological Characterizations Of Ca215-s+ mentioning
confidence: 99%
See 4 more Smart Citations
“…Huang, Wang, Zhang, Li, & Li, 2013) Anastellin 256 (Neskey, Ambesi, Pumiglia, & McKeown-Longo, 2008;Pasqualini, Bourdoulous, Koivunen, Woods, & Ruoslahti, 1996;M. Yi & Ruoslahti, 2001) Apolipoprotein A-1 31 (Macuks et al, 2010;Zamanian-Daryoush et al, 2013) Fibrinogen β chain 56 (Krajewska et al, 2010) Keratin type I cytoskeletal 9 62 (W. Yi et al, 2013) Others: Complement component C4b (Childo blood group) 193 (Markiewski & Lambris, 2009;Rutkowski et al, 2010) …”
Section: Biochemical and Immunological Characterizations Of Ca215-s+ mentioning
confidence: 99%
“…Studies performed using human microvessel endothelial cells have shown that anastellin inhibits serum dependent cell growth by blocking progression of the cell cycle (Neskey et al, 2008). Zamanian-Daryoush et al, 2013). Apolipoprotein A-1 has been shown to be a biomarker of ovarian cancer and in combination with CA215 increased the sensitivity for ovarian cancer detection (Macuks et al, 2010).…”
Section: Anastellinmentioning
confidence: 99%
See 3 more Smart Citations